(untitled) (Biological Sciences - PJSIR, 2022)
Mixed-ligand complexes of Zr (IV) and U(VI) with salicylaldehyde (SA) and some heterocyclic azopyrazoloncs (HAP)have been studicdspcctrophotomeuically. All Connedchelates haveratio 1:1:1.The stiochiornctry and thesta- bilityofthebinaryandmixed chelateshavebeenevaluated. Elementalanalysis,molarconductance andIRspectrahave been used for identification of the solid mixed complexes.